A new Gaussian analytical wake model validated by wind tunnel experiment and LiDAR field measurements under different turbulent flow. (15th May 2023) - Wang, Tengyuan; Cai, Chang; Wang, Xinbao; Wang, Zekun; Chen, Yewen; Song, Juanjuan; Xu, Jianzhong; Zhang, Yuning; Li, Qingan
Abstract: Wind turbine wake has a great effect on wind power generation and fatigue loads of downstream wind turbines in wind farms. Analytical engineering wake model is adopted to evaluate the power loss caused by turbine wake for the optimization of wind farm layout. Gaussian distribution is often employed in wake model. Traditional Gaussian distributions, on the other hand, are unable to accurately describe wind speed especially near the wake boundary. Besides, the variable turbulent environment in wind farms with complex terrain poses a challenge to the turbine wake model. In this paper, the unfitness of the Gaussian wake model especially near the wake boundary is addressed and a Gaussian wake model with new turbulence intensity model is proposed. Compared with previous models, this new wake model has a more suitable wind speed distribution. The new wake model is then validated using wind tunnel measurements under different turbulence intensity. Results indicate that the new Gaussian wake model can more correctly predict the wind turbine wake than the previous Gaussian wake models. The new Gaussian wake model suitable shows a good application prospect in wind farm layout optimization which improves the power generation and reduces the power generation costs. Highlights: A new Gaussian wake model is proposed. Wind tunnel measurements with different turbulence intensity are analyzed. Wake characteristics of wind tunnel measurements and LiDAR measurements are analyzed. The Gaussian wake model shows a good performance under different turbulent flow.